Ultrastructural characterization of the egg chorion and reproductive anatomy of potato tuber moth, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) - Pranita Roy; Suresh R. Jambagi; K. Logeswaran; Doddachowdappa Sagar; M. Mohan; G. Mahendiran; D. Nandhini (Tissue and Cell, 2027)

An explainable deep learning-integrated decision support system for field diagnosis and management of botrytis grey mold in castor - G. Jadesha; Yamanura Madival; R. Mohan Kumar; Anurag Dhole; H.C. Lohithaswa; Mallana Gowda Mallikarjuna; K.B. Palanna; D. Deepak (Computers and Electronics in Agriculture, 2026)

Sensitivity analysis-based multi-objective calibration using machine learning emulators for integral water system models - Meera Mohan; Saumya Srivastava; Leyang Liu; D. Nagesh Kumar; Ana Mijic (Hydrological Sciences Journal, 2026)

Microbial necromass accelerates humic acid formation by reshaping DOM transformation pathways during composting - Su Chang; Yi Zheng; Baoju Liu; Wenjie Chen; Yuquan Wei; Long D. Nghiem; Mohan Bai; Guochun Ding; Huike Ye; Yan Xu; Ji Li (Environmental Research, 2026)

Mineral-driven accumulation of microbial necromass enhanced humification during composting - Wenjie Chen; Yan Yang; Kui Zhang; Su Chang; Yuan Chang; Ji Li; Xia Liang; Yifan Liu; Long D. Nghiem; Mohan Bai; Huike Ye; Zichao Zhao; et al. (Journal of Environmental Chemical Engineering, 2026)

Influence of regional rainfall biases on sub-seasonal variability during boreal summer over South Asia in NGFS reanalysis - Bibhuti S. Keshav; Mohan T. S; Smrutishree Lenka; Nagarjuna Rao D; Raghavendra Ashrit; V.S. Prasad (Dynamics of Atmospheres and Oceans, 2026)

Astrocyte-microglia crosstalk in Lead-induced neurotoxicity: Molecular signaling and downstream pathological sequelae - Suman Maity; Moumita Saha; Zahwa Fathima; Yoshitha Kondeti; Rahul L. Gajbhiye; Mohan Gandhi Bonthu; Shriram D. Ranade; Sudheer Moorkoth; Srinivas Mutalik; Ramalingam Peraman; Pothuraju Naresh (Chemico-Biological Interactions, 2026)

Attitudes of Algorithms: An Exploration of the Ethics of CRISPR Cas9 through the Lens of ChatGPT - Russell Franco D’Souza; Mary Mathew; Krishna Mohan Surapaneni (Indian Journal of Clinical Biochemistry, 2026)

Plant-derived neuroprotective compounds and nanoformulations targeting Parkinson’s disease: a semi-systematic review of mechanisms and therapeutic potential - Saraswathi Saraswathi; Jagadisha Tavarekere Venkataravanappa; Chaithanya Nambiar; Sharon Saji; Vinuta Kori; Mamatha N Murthy; Prabhakara Somanna; Suresh Babu SV; Arun Kumar Sreeramulu; Ashok Dayalan; Sindhu Priya Mohan; Chaithra D Srinivas Murthy (Metabolic Brain Disease, 2026)

Derivation of seawater quality criteria for copper, cadmium, zinc, and mercury for the coastal and coral reef ecosystems of Gulf of Mannar, India - C M Ramakritinan; M Anand; L Palanikumar; Manoj Singh; S Manikandan; G Jayanthi; A K Kumaraguru; D Mohan; T Balasubramanian; B R Subramanian (Journal of Earth System Science, 2026)

Phytochemistry and nutraceutical potential of Ceylon Cinnamomum species native to Sri Lanka - Lakmal Gonawala; Maheehsa Madhumaali; Hanouf Ismail; Nishara Jayasooriya; Nalaka Wijekoon; Shanuk Rajapakshe; Harshanie Erangika; Dhammika Amaratunga; Rajitha Gunaratna; Harry W.M. Steinbusch; Chandra Mohan; Yu-Chung Chiang; et al. (Natural Product Research, 2026)

Investigating moist dynamics on sub-seasonal scales in the IMDAA reanalysis - Mohan T. S.; Smrutishree Lenka; Indira Rani; Niranjan Kumar Kondapalli; Nagarjuna Rao D; Saji Mohandas (Science of The Total Environment, 2026)

Drought-induced modulations in stomatal traits and potential conductance index of citrus rootstock genotypes - Amrut Sanjay Morade; Radha Mohan Sharma; Anil Kumar Dubey; Lekshmy Sathee; Darshan Manikrao Kadam; Ashok Kumar Mahawer; Vijaysinha D. Kakade; Sangram B. Chavan; S. Gurumurthy (Plant Physiology Reports, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Protected areas influence fire regimes globally - A. Cardil; M. Rodrigues; D. Ascoli; M. Ortega; T. Quiñones; M. Erdozain; I. Oliveras Menor; G.L. Spadoni; J. Ramírez; J.R. Molina; F. Mouillot; C.A. Silva; et al. (Journal of Environmental Management, 2026)

Heteroleptic N, N donor carbonitrile based Au(III) complexes: DNA/BSA interaction studies, Molecular Docking, and cytotoxicity studies - Nikita J. Patel; Ravi A. Dabhi; Milan P. Dhaduk; Nirbhay K. Savaliya; Bhupesh S. Bhatt; Miral V. Lunagariya; Vaibhav D. Bhatt; Mohan N. Patel (Journal of Trace Elements in Medicine and Biology, 2025)

Date Palm (Phoenix dactylifera L.) Microsatellites: Genome-Wide Resource for Diversity Analysis and Cross-Transferability in Arecaceae - Darshan T. Dharajiya; Bhemji P. Galvadiya; Piyush Verma; Anuj Kumar Singh; Kapil Mohan Sharma; D. A. Baidiyavadra; C. M. Muralidharan; Kapil K. Tiwari (Sugar Tech, 2025)

Assessment of Genetic Variability of Date Palm (Phoenix dactylifera L.) Grown Under Arid Ecosystem of Gujarat, India - Kapil Mohan Sharma; Piyush Verma; Nishit V. Soni; Kapil K. Tiwari; D. A. Baidiyavadra; Mani N. Chaudhari; Bhargav B. Golakiya; P. C. Joshi (Sugar Tech, 2025)

Mitigating biofouling in cooling water system: Actibromide ® to combat Perna viridis infestation and environmental impact - Bandita Badakumar; D. Inbakandan; S. Venkatnarayanan; T. V. Krishna Mohan; Y. V. Nancharaiah; P. Veeramani; N. K. Pandey; P. Sriyutha Murthy (Biofouling, 2025)

Different distribution patterns and potential risks of pesticide residues between soils and sediments: a case study in Lake Taihu Ecological Conservation Area - Yuyang Hao; Mohan Bai; Lanqing Sun; Shuo Yang; Chunyu Wang; Qing X. Li; Bruce D. Hammock; El-Sayed A. El-Sheikh; Ting Xu (Environmental Monitoring and Assessment, 2025)

Protocol for the in-situ U–Pb dating of zircon with high sample throughput and spatial resolution using LA-HR-ICP-MS: A case study on detrital zircon from the Cuddapah Basin - Sameer Ranjan; Ajay Dev Asokan; M Ram Mohan; M Satyanarayanan; D Srinivasa Sarma (Journal of Earth System Science, 2025)

Glycine betaine mitigates cadmium toxicity in plants via redox homeostasis and osmotic adjustment - Gayatri Devi Biswal; Madhulika Singh; D. K. Patel; Sheo Mohan Prasad (Journal of Plant Biochemistry and Biotechnology, 2025)

Assessment of soybean breeding lines from the all India coordinated research programme for agronomic traits and resistance to mungbean yellow mosaic India virus through field screening and artificial inoculation - Dharmappa D. Chavan; Firoz Mondal; Yeluru Mohan Babu; Mehulee Sarkar; Ainmisha Singh; Halima Khatoon; Sanjay Kumar Lal; Kajal Kumar Biswas; Bikash Mandal; Anirban Roy (Physiology and Molecular Biology of Plants, 2025)

Harvest of algal biomass with bioflocculants for biofuel with upstream and downstream processes: State-of-the-art towards sustainable alternative - Kajol Goria; Richa Kothari; Har Mohan Singh; Deepak Pathania; D. Buddhi; Atul Sharma; V. V. Tyagi (Energy, Ecology and Environment, 2025)

A novel report of Rhizoctonia solani AG-4 HG-I associated with damping-off and wilt of quinoa (Chenopodium quinoa) in India - D. Chethan; R. Chandana; Farooq Khan; B.S. Kavya; T. Tharana Poonacha; R. Karan; Akash Bevanur; R. Kruthika; K.S. Ashwini; Yerranagari Vani; S.R. Anand; A. Mohan Rao; et al. (Physiological and Molecular Plant Pathology, 2025)

Enhancement of genetic gain for early seedling vigor traits through marker-assisted pedigree selection in rice (Oryza sativa L.) - Sudhamani Kalluru; Issa Keerthi; Madhavilatha Kommana; D. M. Withanawasam; Eswarayya Ramireddy; D. Mohan Reddy; V. Umamahesh; Lakshminarayana R. Vemireddy (Physiology and Molecular Biology of Plants, 2025)

Zircon U-Pb age and petrogenetic constraints on granitic magmatism from the southwestern Chhotanagpur Granite Gneiss Complex: Implications for Proterozoic crustal growth in the Central India - Mohammad Qasim; Satya Narayana Mahapatro; Sameer Ranjan; Ajay Dev Asokan; D. Srinivasa Sarma; M. Ram Mohan (Precambrian Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Fidelity of coupled hindcast simulations in representing intraseasonal biases over South Asia - D. Nagarjuna Rao; T. S. Mohan; Ankur Gupta; Kondapalli Niranjan Kumar; Akhilesh Mishra; Imranali M. Momin; Saji Mohandas; Ashis K. Mitra; V. S. Prasad (Climate Dynamics, 2025)

Importance of solenoid valve selection for performance of a cold gas thruster for an orbital experimental module - N. Venkata Sunil Sai; Arnika Verma; A. Sanoj; G. Yaswanth Ram; K. Muthuselvi; D. Venkittaraman; K. Krishna Mohan Shanbhogue; Subrata Chakrabarti (Advances in Space Research, 2025)

Versatile MnFeCO3@Ni1-xCo0xZnMoO4 O-rich perovskite and bio-derived carbon for energy storage and conversion devices - Samikannu Prabu; Madhan Vinu; Kung-Yuh Chiang; Munirah D. Albaqami; Saikh Mohammad; Mohan Reddy Pallavolu; Kummara Madhusudana Rao (Chemical Engineering Journal, 2025)

Early insights into the seasonal and spatial distribution of white sharks (Carcharodon carcharias) along the Maine coastline - Matthew M. Davis; Megan V. Winton; John A. Mohan; Joseph D. Iafrate; James A. Sulikowski; Blaise P. Jenner; Ashleigh J. Novak; Victoria Migneco; Tobey H. Curtis; Chip Michalove; Gregory B. Skomal (Frontiers in Marine Science, 2025)
While significant progress has been made to characterize life history patterns, movement ecology, and regional estimates of abundance of white sharks ( Carcharodon carcharias ) in the Western North Atlantic (WNA), patterns of spatial distribution remain relatively unknown in the northern Gulf of Maine. In this study, we utilize data collected from multiple acoustic telemetry projects from 2012-2023 to assess the spatiotemporal distribution of white sharks along sections of the Maine coastline and regional offshore waters. Acoustic receivers were deployed each year from 2012-2019 (mean number of receivers ± SD: 11 ± 4), and effort increased following the first-ever white shark related fatality in Maine in 2020 (2020-2023: 40 ± 15). In total, 107 white sharks tagged by researchers in the WNA were detected, with the majority (n = 90) detected in shallow (<50 m depth) waters post-2019. Reflective of the tagged population at-large, total length of individuals ranged from 2.1 to 4.9 m, with most individuals estimated to be in the juvenile or subadult life stages. White sharks were detected between the months of May-December, with peaks between July and September, and were observed in close proximity to several of Maine’s western beaches and islands/outcroppings, with higher numbers observed at several sites in eastern Casco Bay. Although the overall quantity of detections was relatively low when compared to white shark aggregation sites in other regions, this study provides baseline information on the presence of this species in the northern Gulf of Maine. While future research should include expanded receiver coverage in eastern Maine and the use of additional tagging technologies, this study contributes early insights for informing marine spatial planning, fisheries management, and conservation strategies for white sharks in the region.

Thermodynamics link with lightning incidents in Tamil Nadu, India - S Kokilavani; V Geethalakshmi; S P Ramanathan; S D Pawar; V Gopalakrishnan; Somnath Mahapatra; Jayesh Chhagan Dhangar; Ga Dheebakaran; N K Sathyamoorthy; M Selva Kumar; S Mohan Kumar; Manoj A Domkawale (Journal of Earth System Science, 2024)

Assessment of Management Practices for Improving Productivity, Profitability, and Energy-Carbon-Water Use Efficiency of Intensive Rice-toria-Sweet Corn System in Eastern India - Stuti Debapriya Behera; Lalita Mohan Garnayak; Biswaranjan Behera; Basudev Behera; Sukanta Kumar Sarangi; Jagadish Jena; Swosti D. Behera; Sanat K. Dwibedi (Journal of Soil Science and Plant Nutrition, 2024)

Boosting the response characteristics towards rapid detection of NO2 gas molecules utilizing 2D - WS2/rGO hybrid nanocomposites at ambient environment - D. Simon Patrick; J. Archana; M. Navaneethan; M. Krishna Mohan (Journal of Environmental Chemical Engineering, 2024)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Nutrient dynamics and sustainability of short rotation Eucalyptus camaldulensis plantations in southern India - Roby Mathew; D. S. Guru Murthy; Mohan Varghese (New Forests, 2024)

Assessment of extreme rainfall events for iFLOWS Mumbai in NCUM regional forecasting system - Mohan S. T; Raghavendra Ashrit; Kondapalli Niranjan Kumar; Upal Saha; D. Nagarjuna Rao; A. Jayakumar; Saji Mohandas; V. S. Prasad (Natural Hazards, 2024)

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

Nutrient dynamics in small west-flowing tropical mountainous rivers of India - S. Kiran Kumar Reddy; Harish Gupta; Vamshi Krishna Gandla; D. Venkat Reddy; Rama Mohan Kurakalva; Devender Kumar (Applied Geochemistry, 2024)

Soil Carbon Sequestration and Agronomic Productivity as Influenced by the Long-Term Organic and Inorganic Fertilisation Under the Upland Rice–Wheat System in Vertisols of Central India - Ch. Srinivasarao; Sumanta Kundu; D. P. Dubey; Rajiv Dubey; S. Rakesh; Rattan Lal; P. C. Abhilash; J. V. N. S. Prasad; G. Pratibha; Somasundaram Jayaraman; K. Mrunalini; K. A. Gopinath; et al. (Anthropocene Science, 2024)

Carbon Stocks of Forests and Tree Plantations Along an Elevational Gradient in the Western Ghats: Does Plant Diversity Impact Forest Carbon Stocks? - B. Mohan Kumar; D. Balasubramanian (Anthropocene Science, 2024)

Physiological and biochemical response in green mussel Perna viridis subjected to continuous chlorination: Perspective on cooling water discharge criteria - Bandita Badakumar; D. Inbakandan; S. Venkatnarayanan; T.V. Krishna Mohan; Y.V. Nancharaiah; N.K. Pandey; P. Veeramani; P. Sriyutha Murthy (Chemosphere, 2024)

Sensitivity analysis of cumulus and microphysics schemes in the WRF model in simulating Extreme Rainfall Events over the hilly terrain of Nagaland - Rupraj Biswasharma; N. Umakanth; Imlisunup Pongener; Imolemba Longkumer; K. Madan Mohan Rao; Sunil D. Pawar; V. Gopalkrishnan; Sanjay Sharma (Atmospheric Research, 2024)

Harnessing nature's arsenal: Ochrobactrum bacteria metabolites in the battle against root- knot nematode – Insights from in vitro and molecular docking studies - V.P Krithika; Ganeshan Shandeep; Anita Bellie; J. Gulsar Banu; Jayakanthan Mannu; M. Suganthy; V. Gomathi; D. Uma; Prasanthrajan Mohan (Journal of Invertebrate Pathology, 2024)

Chemical composition and biological activities of Lonicera caprifolium L. (Caprifoliaceae) essential oil - Anjali A. Gavit; Manish B. Gagrani; Shailendra S. Gurav; M. Ayyanar; Vishal G. Beldar; Anilkumar U. Tatiya; Sanjay J. Surana; Sandip D. Firke; Mohan G. Kalaskar (Natural Product Research, 2024)

Biomass pretreatment with distillable ionic liquids for an effective recycling and recovery approach - Ezinne C. Achinivu; Brian W. Blankenship; Nawa Raj Baral; Hemant Choudhary; Ramu Kakumanu; Mood Mohan; Edward E.K. Baidoo; Corinne D. Scown; Anthe George; Blake A. Simmons; John Gladden (Chemical Engineering Journal, 2024)

Efficacy of surfactants in the sustainable restoration of the geotechnical properties of diesel-contaminated soil - A. Kumar; D. Mohan; B. R. Paramkusam; A. P. Singh (International Journal of Environmental Science and Technology, 2024)

High-resolution insights of physical properties of water columns of lakes at the Larsemann Hills, East Antarctica - Cheryl A. Noronha-D’Mello; B.S. Mahesh; Jenson George; Shramik Patil; Avirajsinh Jadav; Rahul Mohan (Polar Science, 2023)

On the simulations of latent heat flux over the Indian Ocean in CMIP6 models - Soumya Mohan; R. D. Ruchith (Climate Dynamics, 2023)

Influence of quantity, quality, horizontal and vertical distribution of ground control points on the positional accuracy of UAV survey - Dharshan Shylesh D S; Manikandan N; Sivasankar S; Surendran D; Jaganathan R; Mohan G (Applied Geomatics, 2023)

Latent heat flux variability over the tropical Indian Ocean - Soumya Mohan; R. D. Ruchith; S. Rahul; P. R. Shanas (International Journal of Climatology, 2023)
The seasonal evolution and interannual variability of latent heat flux (LHF) over the tropical Indian Ocean (TIO) region is examined for the period 1980–2019. The seasonal distribution of LHF is dominated by the winter pattern of each hemisphere in the TIO. Climatologically high LHF is mostly confined to the Arabian Sea and Bay of Bengal regions in the north Indian Ocean and the zonal belt between 10 o S and 25 o S in the south Indian Ocean. Warm and cold phases of El‐Niño Southern Oscillation, Indian Ocean Dipole (IOD), and their co‐occurrence events leave distinct LHF signatures over the TIO. The LHF anomalies during these events are more profound than pure events with enhanced latent heat loss when the La Niña and negative IOD events coincide. The LHF anomalies associated with the wind‐evaporation‐SST feedback is prominent when positive IOD co‐occur with the El‐Niño event. Both the vertical humidity gradient and wind speed changes play substantial roles in driving LHF anomalies during the co‐occurring events of NIOD and La Niña.

Optimization of Survey Area for Auriferous-Sulphide Mineralization Using Integrated Geophysical Study: A Case Study from Gani-Kalva Fault Zone, Cuddapah Basin, India - D. Vijayakumar; M. Mohan Babu; G. Srinivasa Rao; G. Rohit; D. G. Madhusudhan (Pure and Applied Geophysics, 2023)

Enhancing the prediction of IDC breast cancer staging from gene expression profiles using hybrid feature selection methods and deep learning architecture - Akash Kishore; Lokeswari Venkataramana; D. Venkata Vara Prasad; Akshaya Mohan; Bhavya Jha (Medical & Biological Engineering & Computing, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Dopant-driven recombination delay and ROS enhancement in nanoporous Cd1-xCuxS heterogeneous photocatalyst for the degradation of DR-23 dye under visible light irradiation - Savita Meena; Mukul Sethi; Swati Meena; Pratibha Saini; Krishan Kumar; Surendra Saini; Sumita Shekhawat; Mohan Lal Meena; Anshu Dandia; Shawn D. Lin; Vijay Parewa (Environmental Research, 2023)

Potential of biogenic and non-biogenic waste materials as flocculant for algal biomass harvesting: Mechanism, parameters, challenges and future prospects - Har Mohan Singh; Mriduta Sharma; V.V. Tyagi; Kajol Goria; D. Buddhi; Atul Sharma; Frank Bruno; Shane Sheoran; Richa Kothari (Journal of Environmental Management, 2023)

Investigating underground water salinity in east coastline of Tamil Nadu, India and improving its quality through solar assisted desalination - V. Kanchana; P. Manoj Kumar; P. Suresh Kumar; I. Kathir; R. Thirumalai; D. Priya; R. Puviarasi; M. Mohan Prasad (Urban Climate, 2023)

Heavy metal contamination in river water, sediment, groundwater and human blood, from Kanpur, Uttar Pradesh, India - Varsha Gupta; Dinesh Kumar; Anamika Dwivedi; Umesh Vishwakarma; D. S. Malik; Seema Paroha; Narendra Mohan; Neelima Gupta (Environmental Geochemistry and Health, 2023)

Multiple traces of monkeypox detected in non-sewered wastewater with sparse sampling from a densely populated metropolitan area in Asia - Dhammika Leshan Wannigama; Mohan Amarasiri; Parichart Hongsing; Cameron Hurst; Charin Modchang; Sudarat Chadsuthi; Suparinthon Anupong; Phatthranit Phattharapornjaroen; Ali Hosseini Rad S.M.; Stefan Fernandez; Angkana T. Huang; Naris Kueakulpattana; et al. (Science of The Total Environment, 2023)

Petrogenesis of Meso-Neoarchean granitoids from the Chitradurga Greenstone Belt: Implications on crustal growth and reworking of the Dharwar Craton, southern India - M. Ram Mohan; Neal J. McNaughton; D. Srinivasa Sarma; M. Rajamanickam; Ian R. Fletcher; Simon A. Wilde; Birger Rasmussen; Bryan Krapež; S. Balakrishnan (Journal of Asian Earth Sciences, 2023)

Identification of genomic regions governing moisture and heat stress tolerance employing association mapping in rice (Oryza sativa L.) - Madhavilatha Kommana; D. Mohan Reddy; K. Amarnath; M. Vinod Kumar Naik; D. M. Withanawasam; Reddyyamini Bommisetty; K. Maneesha; M. Bhargavi; Aparna Eragam; B. V. Bhaskara Reddy; P. Sudhakar; Lalam Krishna; et al. (Molecular Biology Reports, 2023)

Genome-wide analysis reveals the crucial role of lncRNAs in regulating the expression of genes controlling pollen development - Neeta Lohani; Agnieszka A. Golicz; Annapurna D. Allu; Prem L. Bhalla; Mohan B. Singh (Plant Cell Reports, 2023)

Identification of molecular markers and putative candidate genes associated with early seedling vigour traits in rice (Oryza sativa L.) - Sudhamani Kalluru; Lakshminarayana R. Vemireddy; Eswarayya Ramireddy; D. Mohan Reddy; V. Umamahesh (Brazilian Journal of Botany, 2022)

Year-round sustainable biomass production potential of Nannochloris sp. in outdoor raceway pond enabled through strategic photobiological screening - Kenny Paul; Mahadev Gaikwad; Poonam Choudhary; Natarajan Mohan; Puja Pai; Smita D. Patil; Yogesh Pawar; Akshay Chawande; Arun Banerjee; Vinod Nagle; Meenakshi Chelliah; Ajit Sapre; et al. (Photosynthesis Research, 2022)

Soil carbon pools under rubber (Hevea brasiliensis) based agroforestry systems in South India - Phebe Joseph; M. D. Jessy; Mahesh Mohan (Agroforestry Systems, 2022)

Chemistry Manufacturing and Controls Development, Industry Reflections on Manufacture, and Supply of Pandemic Therapies and Vaccines - Matthew E. Popkin; Markus Goese; Diane Wilkinson; Stuart Finnie; Talia Flanagan; Cristiana Campa; Alexandra Clinch; Andrew Teasdale; Andrew Lennard; Graham Cook; Ganapathy Mohan; Matthew D. Osborne (The AAPS Journal, 2022)

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Multi-drug resistant (MDR), extended spectrum beta-lactamase (ESBL) producing and carbapenem resistant Escherichia coli in rescued Sloth bears (Melursus ursinus), India - O. R. VinodhKumar; M. Karikalan; S. Ilayaraja; Arun A. Sha; B. R. Singh; D. K. Sinha; S. Chandra Mohan; B. S. Pruthvishree; A. M. Pawde; A. K. Sharma (Veterinary Research Communications, 2021)

Eliciting heavy metal contamination on selected native organisms from Cochin estuary using contemporary biomarker approach - N D Don Xavier; S Bijoy Nandan; P R Jayachandran; K V Neethu; D Mohan; S R Marigoudar (Journal of Earth System Science, 2021)

Potential suitable habitat of Buckwheat (Fagopyrum spp) under the climate change scenarios in Nepal - Dol Raj Luitel; Mohan Siwakoti; Mohan D. Joshi; Muniappan Rangaswami; Pramod K. Jha (Journal of Crop Science and Biotechnology, 2021)

A dynamic intron retention program regulates the expression of several hundred genes during pollen meiosis - Agnieszka A. Golicz; Annapurna D. Allu; Wei Li; Neeta Lohani; Mohan B. Singh; Prem L. Bhalla (Plant Reproduction, 2021)

Semaphorin3F Drives Dendritic Spine Pruning Through Rho-GTPase Signaling - Bryce W. Duncan; Vishwa Mohan; Sarah D. Wade; Young Truong; Alexander Kampov-Polevoi; Brenda R. Temple; Patricia F. Maness (Molecular Neurobiology, 2021)

Genome Guided Bioprospecting of Extremely Halophilic Haloferax sp. AS1 for CAZymes, Bioremediation and Study Metabolic Versatility - Milind Mohan Naik; Md. Imran; Diviya C. Vaigankar; Sajiya Yusuf Mujawar; Alisha D. Malik; Sanket K. Gaonkar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

A novel barcode system for rapid identification of rice (Oryza sativa L.) varieties using agro-morphological descriptors and molecular markers - M. Bhargavi; K. Maneesha; D. M. Withanawasam; Kavitha R. Aratikatla; S. Himabindu; M. Prashanth; P. Shanthi; Madhavi L. Kommana; D. Mohan Reddy; B. Ravindra Reddy; Lakshminarayana R. Vemireddy (Molecular Biology Reports, 2021)

Evaluation of Potentiality of Different Adjuvants for Date Palm Pollination and Fruit Set - Kapil Mohan Sharma; C. M. Muralidharan; D. A. Baidiyavadra; Kirti Bardhan; C. N. Panchal (Sugar Tech, 2021)

Pistillate Receptivity of Date Palm (Phoenix dactylifera L.) cv. Barhee - C. M. Muralidharan; C. N. Panchal; D. A. Baidiyavadra; Kapil Mohan Sharma; Piyush Verma (Sugar Tech, 2020)

The mechanisms of biochar interactions with microorganisms in soil - Andrey V. Gorovtsov; Tatiana M. Minkina; Saglara S. Mandzhieva; Leonid V. Perelomov; Gerhard Soja; Inna V. Zamulina; Vishnu D. Rajput; Svetlana N. Sushkova; Dinesh Mohan; Jun Yao (Environmental Geochemistry and Health, 2020)

Perchlorate contamination of drinking water sources in Kerala, South India, and its degradation using advanced chemical treatment - M. R. Sijimol; C. T. Aravindakumar; P. R. Manoj; D. Dineep; K. K. Nejumal; Mahesh Mohan (Energy, Ecology and Environment, 2020)

Oceanographic Structure and Light Levels Drive Patterns of Sound Scattering Layers in a Low-Latitude Oceanic System - Kevin M. Boswell; Marta D’Elia; Matthew W. Johnston; John A. Mohan; Joseph D. Warren; R. J. David Wells; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Adaptive Neuro-Fuzzy Inference System-Based Exploration of the Interrelationships of 25-Hydroxyvitamin D, Calcium, Phosphorus with Parathyroid Hormone Production - Iyyapu Krishna Mohan; Siraj Ahmed Khan; D. Shiva Krishna; M. Vijaya Bhaskar; K. S. S. Sai Baba; Tajamul Hussain; Salman A. Alrokayan; Shaik Mohammad Naushad (Indian Journal of Clinical Biochemistry, 2020)

Terminalia arjuna extract and arjunic acid mitigate cobalt chloride–induced hypoxia stress–mediated apoptosis in H9c2 cells - T. Mohan Manu; T. Anand; M. D. Pandareesh; P. Bhuvanesh Kumar; Farhath Khanum (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Rapid seismic hazard assessment of the Sabarmati River basin in Gujarat State, Western India using GIS techniques - Nisarg Bhatt; Vasu Pancholi; Sumer Chopra; Madan Mohan Rout; R. D. Shah; Girish Ch. Kothyari (Bulletin of Engineering Geology and the Environment, 2019)

Symbiotic Response of Drought Tolerant Soybean Varieties, DSR 2 and DSR 12 to Different Arbuscular Mycorrhizal Fungi - R. Ashwin; D. J. Bagyaraj; B. Mohan Raju (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Recombinant Partial Conglutinin of Buffalo and Nilgai In Vitro Can Mimic the Functions of Native Conglutinin In Vivo - D. Ramesh; S. Chandra Mohan; Mohini Saini; Sasmita Barik; M. Shynu; Asit Das; Anil Kumar Sharma; Vinod Kumar Chaturvedi; Praveen Kumar Gupta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Trends and homogeneity of monthly, seasonal, and annual rainfall over arid region of Rajasthan, India - Hari Mohan Meena; Deepesh Machiwal; Priyabrata Santra; Pratap Chandra Moharana; D. V. Singh (Theoretical and Applied Climatology, 2019)

Environmental impact assessment studies for mining area in Goa, India, using the new approach - Manan Sarupria; Sampatrao D. Manjare; Mohan Girap (Environmental Monitoring and Assessment, 2019)

Integrating Multiple Natural Tags to Link Migration Patterns and Resource Partitioning Across a Subtropical Estuarine Gradient - John A. Mohan; Benjamin D. Walther (Estuaries and Coasts, 2018)

Presence of bisphenol S and surfactants in the sediments of Kongsfjorden: a negative impact of human activities in Arctic? - K. K. Nejumal; D. Dineep; Mahesh Mohan; K. P. Krishnan; U. K. Aravind; C. T. Aravindakumar (Environmental Monitoring and Assessment, 2018)

Design, synthesis and fluorescence property evaluation of blue emitting triazole-linked chromene peptidomimetics - T. Jency Mohan; D. Bahulayan (Molecular Diversity, 2017)

Environmental degradation of a tropical estuary due to human interferences—a case study from southern Kerala, SW India - Shiekha E. John; T. R. Rajimol; Vishnu Mohan S; K. Maya; D. Padmalal (Arabian Journal of Geosciences, 2017)

Factors shaping the co-occurrence of two juvenile shark species along the Texas Gulf Coast - Philip Matich; John A. Mohan; Jeffrey D. Plumlee; Tom TinHan; R. J. David Wells; Mark Fisher (Marine Biology, 2017)

Perchlorate in drinking water around rocket manufacturing and testing facilities and firework manufacturing sites in Kerala, India - M. R. Sijimol; V. G. Gopikrishna; D. Dineep; Mahesh Mohan (Energy, Ecology and Environment, 2017)

Biochemical and Histopathological Changes Induced by Nickel in the Striped Mullet, Mugil cephalus (Linnaeus 1758) - A. Nagarjuna; D. Mohan (Bulletin of Environmental Contamination and Toxicology, 2017)

High-fructose diet is as detrimental as high-fat diet in the induction of insulin resistance and diabetes mediated by hepatic/pancreatic endoplasmic reticulum (ER) stress - M. Balakumar; L. Raji; D. Prabhu; C. Sathishkumar; P. Prabu; V. Mohan; M. Balasubramanyam (Molecular and Cellular Biochemistry, 2016)

Fatty‐acid biomarkers and tissue‐specific turnover: validation from a controlled feeding study in juvenile A tlantic croaker Micropogonias undulatus - S. D. Mohan; J. A. Mohan; T. L. Connelly; B. D. Walther; J. W. McClelland (Journal of Fish Biology, 2016)
Fatty‐acid ( FA ) profiles of liver and muscle tissue from juvenile Atlantic croaker Micropogonias undulatus were examined over a 15 week diet‐switch experiment to establish calibration coefficients ( CC ) and improve understanding of consumer–diet relationships for field applications. Essential FAs [docosahexaenoic acid ( DHA ), 22:6n‐3 and eicosapentaenoic acid ( EPA ) , 20:5n‐3] decreased and 18:2n‐6 increased in tissues of M. undulatus fed diets with increasing proportions of terrestrial v. marine lipid sources. Non‐linear models used to estimate the incorporation rate and days to saturation of per cent 18:2n‐6 in tissues showed that livers incorporated 18:2n‐6 faster than muscle, but the proportions of 18:2n‐6 in muscle were higher. CCs were established to determine proportions of FA deposition in tissues relative to diet. Many CCs were consistent amongst diet treatments, despite growth and dietary differences. The CCs can be used to discern FA modification and retention within tissues and as tools for future quantitative estimates of diet histories. Incorporation rates and CCs of 18:2n‐6 were applied to a sub‐set of field samples of wild M. undulatus to understand habitat use and feeding ecology. Altogether, these results suggest that FAs provide a time‐integrated measure of diet in aquatic food webs and are affected by tissue type, growth rate and the influence of mixed diets.

Optimization of Wastewater Anaerobic Digestion Using Mechanistic and Meta-heuristic Methods: Current Limitations and Future Opportunities - P. E. Poh; D. Gouwanda; Y. Mohan; A. A. Gopalai; H. M. Tan (Water Conservation Science and Engineering, 2016)

Perchlorate contamination in bottled and other drinking water sources of Kerala, southwest coast of India - M. R. Sijimol; Mahesh Mohan; D. Dineep (Energy, Ecology and Environment, 2016)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Dose calculation, design and development of nateglinide matrix tablets using quality by design approach and its pharmacokinetic evaluation in animal model - Sudheer Betha; B. Pamula Reddy; P. V. Swamy; M. Mohan Varma; D. Basava Raju; Venkata Ramana Murthy Kolapalli (Journal of Pharmaceutical Investigation, 2015)

Spatiotemporal Variation of Trace Elements and Stable Isotopes in Subtropical Estuaries: II. Regional, Local, and Seasonal Salinity-Element Relationships - John A. Mohan; Benjamin D. Walther (Estuaries and Coasts, 2015)

Development of simvastatin electrospun fibers: a novel approach for sustained drug delivery - Sudheer Betha; B. Pamula Reddy; M. Mohan Varma; D. Basava Raju; Venkata Ramana Murthy Kolapalli (Journal of Pharmaceutical Investigation, 2015)

Microwave-assisted synthesis of novel 1,2,3-triazole derivatives and their antimicrobial activity - D. Ashok; D. Mohan Gandhi; G. Srinivas; A. Vikas Kumar (Medicinal Chemistry Research, 2014)

Increased circulatory levels of lipopolysaccharide (LPS) and zonulin signify novel biomarkers of proinflammation in patients with type 2 diabetes - B. Jayashree; Y. S. Bibin; D. Prabhu; C. S. Shanthirani; K. Gokulakrishnan; B. S. Lakshmi; V. Mohan; M. Balasubramanyam (Molecular and Cellular Biochemistry, 2014)

Nasal delivery of PLG microparticle encapsulated defensin peptides adjuvanted gp41 antigen confers strong and long-lasting immunoprotective response against HIV-1 - Teena Mohan; D. Mitra; D. N. Rao (Immunologic Research, 2014)

Comparative In-Vitro Functional Analysis of Synthetic Defensins and Their Corresponding Peptide Variants Against HIV-1NL4.3, E. coli, S. aureus and P. aeruginosa - T. Mohan; D. Mitra; D. N. Rao (International Journal of Peptide Research and Therapeutics, 2013)

Mapping QTL for grain yield and other agronomic traits in post-rainy sorghum [Sorghum bicolor (L.) Moench] - R. Nagaraja Reddy; R. Madhusudhana; S. Murali Mohan; D. V. N. Chakravarthi; S. P. Mehtre; N. Seetharama; J. V. Patil (Theoretical and Applied Genetics, 2013)

Altered dynamics of forest recovery under a changing climate - Kristina J. Anderson‐Teixeira; Adam D. Miller; Jacqueline E. Mohan; Tara W. Hudiburg; Benjamin D. Duval; Evan H. DeLucia (Global Change Biology, 2013)
Forest regeneration following disturbance is a key ecological process, influencing forest structure and function, species assemblages, and ecosystem–climate interactions. Climate change may alter forest recovery dynamics or even prevent recovery, triggering feedbacks to the climate system, altering regional biodiversity, and affecting the ecosystem services provided by forests. Multiple lines of evidence – including global‐scale patterns in forest recovery dynamics; forest responses to experimental manipulation of CO 2 , temperature, and precipitation; forest responses to the climate change that has already occurred; ecological theory; and ecosystem and earth system models – all indicate that the dynamics of forest recovery are sensitive to climate. However, synthetic understanding of how atmospheric CO 2 and climate shape trajectories of forest recovery is lacking. Here, we review these separate lines of evidence, which together demonstrate that the dynamics of forest recovery are being impacted by increasing atmospheric CO 2 and changing climate. Rates of forest recovery generally increase with CO 2 , temperature, and water availability. Drought reduces growth and live biomass in forests of all ages, having a particularly strong effect on seedling recruitment and survival. Responses of individual trees and whole‐forest ecosystems to CO 2 and climate manipulations often vary by age, implying that forests of different ages will respond differently to climate change. Furthermore, species within a community typically exhibit differential responses to CO 2 and climate, and altered community dynamics can have important consequences for ecosystem function. Age‐ and species‐dependent responses provide a mechanism by which climate change may push some forests past critical thresholds such that they fail to recover to their previous state following disturbance. Altered dynamics of forest recovery will result in positive and negative feedbacks to climate change. Future research on this topic and corresponding improvements to earth system models will be a key to understanding the future of forests and their feedbacks to the climate system.

Fentanyl-associated Fatalities Among Illicit Drug Users in Wayne County, Michigan (July 2005–May 2006) - D. Adam Algren; Carolyn P. Monteilh; Mohan Punja; Joshua G. Schier; Martin Belson; Bradford R. Hepler; Carl J. Schmidt; Corinne E. Miller; Manish Patel; Leonard J. Paulozzi; Masja Straetemans; Carol Rubin (Journal of Medical Toxicology, 2013)

Density estimation in tiger populations: combining information for strong inference - Arjun M. Gopalaswamy; J. Andrew Royle; Mohan Delampady; James D. Nichols; K. Ullas Karanth; David W. Macdonald (Ecology, 2012)
A productive way forward in studies of animal populations is to efficiently make use of all the information available, either as raw data or as published sources, on critical parameters of interest. In this study, we demonstrate two approaches to the use of multiple sources of information on a parameter of fundamental interest to ecologists: animal density. The first approach produces estimates simultaneously from two different sources of data. The second approach was developed for situations in which initial data collection and analysis are followed up by subsequent data collection and prior knowledge is updated with new data using a stepwise process. Both approaches are used to estimate density of a rare and elusive predator, the tiger, by combining photographic and fecal DNA spatial capture–recapture data. The model, which combined information, provided the most precise estimate of density (8.5 ± 1.95 tigers/100 km 2 [posterior mean ± SD]) relative to a model that utilized only one data source (photographic, 12.02 ± 3.02 tigers/100 km 2 and fecal DNA, 6.65 ± 2.37 tigers/100 km 2 ). Our study demonstrates that, by accounting for multiple sources of available information, estimates of animal density can be significantly improved.

Impact of Annular Solar Eclipse of 15 January 2010 on the Atmospheric Boundary Layer Characteristics Over Thumba: A Case Study - D. Bala Subrahamanyam; T. J. Anurose; Mannil Mohan; M. Santosh; N. V. P. Kiran Kumar; S. Sijikumar (Pure and Applied Geophysics, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Atmospheric Surface-Layer Response to the Annular Solar Eclipse of 15 January 2010 over Thiruvananthapuram, India - D. Bala Subrahamanyam; T. J. Anurose; Mannil Mohan; M. Santosh; N. V. P. Kiran Kumar; S. Sijikumar; S. S. Prijith; Marina Aloysius (Boundary-Layer Meteorology, 2011)

Archaean gold mineralization synchronous with late cratonization of the Western Dharwar Craton, India: 2.52 Ga U–Pb ages of hydrothermal monazite and xenotime in gold deposits - D. Srinivasa Sarma; Ian R. Fletcher; Birger Rasmussen; Neal J. McNaughton; M. Ram Mohan; David I. Groves (Mineralium Deposita, 2011)

Identification of quantitative trait loci associated with resistance to foliar diseases in sorghum [Sorghum bicolor (L.) Moench] - S. Murali Mohan; R. Madhusudhana; K. Mathur; D. V. N. Chakravarthi; Sanjay Rathore; R. Nagaraja Reddy; K. Satish; G. Srinivas; N. Sarada Mani; N. Seetharama (Euphytica, 2010)

Carbon storage in relation to soil size-fractions under tropical tree-based land-use systems - Subhrajit K. Saha; P. K. Ramachandran Nair; Vimala D. Nair; B. Mohan Kumar (Plant and Soil, 2010)

Decreased mass specific respiration under experimental warming is robust to the microbial biomass method employed - Mark A. Bradford; Matthew D. Wallenstein; Steven D. Allison; Kathleen K. Treseder; Serita D. Frey; Brian W. Watts; Christian A. Davies; Thomas R. Maddox; Jerry M. Melillo; Jacqueline E. Mohan; James F. Reynolds (Ecology Letters, 2009)
Hartley et al. question whether reduction in R mass , under experimental warming, arises because of the biomass method. We show the method they treat as independent yields the same result. We describe why the substrate‐depletion hypothesis may not solely explain observed responses, and urge caution in interpretation of the seasonal data.

Soil carbon stock in relation to plant diversity of homegardens in Kerala, India - Subhrajit K. Saha; P. K. Ramachandran Nair; Vimala D. Nair; B. Mohan Kumar (Agroforestry Systems, 2009)

Origin and characterisation of microparticles in an ice core from the Central Dronning Maud Land, East Antarctica - C. M. Laluraj; K. P. Krishnan; M. Thamban; R. Mohan; S. S. Naik; W. D’Souza; R. Ravindra; A. Chaturvedi (Environmental Monitoring and Assessment, 2009)

Evaluation of rice–legume–rice cropping system on grain yield, nutrient uptake, nitrogen fixation, and chemical, physical, and biological properties of soil - Dwipendra Thakuria; Narayan C. Talukdar; Chandan Goswami; Samarendra Hazarika; Mohan C. Kalita; Gary D. Bending (Biology and Fertility of Soils, 2009)

The proteoglycan bamacan is a host cellular ligand of vaccinia virus neurovirulence factor N1L - Ketha VK Mohan; Cheryl X Zhang; Chintamani D Atreya (Journal of NeuroVirology, 2009)

Defective rotavirus particle assembly in lovastatin-treated MA104 cells - Ketha V. Mohan; Jacqueline Muller; Chintamani D. Atreya (Archives of Virology, 2008)

Thermal adaptation of soil microbial respiration to elevated temperature - Mark A. Bradford; Christian A. Davies; Serita D. Frey; Thomas R. Maddox; Jerry M. Melillo; Jacqueline E. Mohan; James F. Reynolds; Kathleen K. Treseder; Matthew D. Wallenstein (Ecology Letters, 2008)
In the short‐term heterotrophic soil respiration is strongly and positively related to temperature. In the long‐term, its response to temperature is uncertain. One reason for this is because in field experiments increases in respiration due to warming are relatively short‐lived. The explanations proposed for this ephemeral response include depletion of fast‐cycling, soil carbon pools and thermal adaptation of microbial respiration. Using a > 15 year soil warming experiment in a mid‐latitude forest, we show that the apparent ‘acclimation’ of soil respiration at the ecosystem scale results from combined effects of reductions in soil carbon pools and microbial biomass, and thermal adaptation of microbial respiration. Mass‐specific respiration rates were lower when seasonal temperatures were higher, suggesting that rate reductions under experimental warming likely occurred through temperature‐induced changes in the microbial community. Our results imply that stimulatory effects of global temperature rise on soil respiration rates may be lower than currently predicted.

Development of tomato hybrids resistant to tomato leaf curl virus disease in South India - K. S. Shankarappa; Sriharsha; K. T. Rangaswamy; D. S. Aswathanarayana; H. A. Prameela; R. S. Kulkarni; V. Muniyappa; A. Mohan Rao; M. N. Maruthi (Euphytica, 2008)

Development of genic-microsatellite markers for sorghum staygreen QTL using a comparative genomic approach with rice - G. Srinivas; K. Satish; S. Murali Mohan; R. Nagaraja Reddy; R. Madhusudhana; D. Balakrishna; B. Venkatesh Bhat; C. J. Howarth; N. Seetharama (Theoretical and Applied Genetics, 2008)

High doses of dietary zinc induce cytokines, chemokines, and apoptosis in reproductive tissues during regression - N. R. Sundaresan; D. Anish; K. V. H. Sastry; V. K. Saxena; K. Nagarajan; J. Subramani; M. D. M. Leo; N. Shit; J. Mohan; M. Saxena; K. A. Ahmed (Cell and Tissue Research, 2008)

Physiogenomic Analysis of Localized fMRI Brain Activity in Schizophrenia - Andreas Windemuth; Vince D. Calhoun; Godfrey D. Pearlson; Mohan Kocherla; Kanchana Jagannathan; Gualberto Ruaño (Annals of Biomedical Engineering, 2008)

Soil contamination of heavy metals in the Katedan Industrial Development Area, Hyderabad, India - P. K. Govil; J. E. Sorlie; N. N. Murthy; D. Sujatha; G. L. N. Reddy; Kim Rudolph-Lund; A. K. Krishna; K. Rama Mohan (Environmental Monitoring and Assessment, 2008)

Activity-directed-fractionation and isolation of four antibacterial compounds from Abrus precatorius L., roots - G. B. Zore; V. Awad; A. D. Thakre; U. K. Halde; N. S. Meshram; B. S. Surwase; S. Mohan Karuppayil (Natural Product Research, 2007)

Spatial dispersion of surface waves at the free surface of a general anisotropic elastic medium - Mohan D. Sharma (Journal of Seismology, 2007)

Seasonal variation of pteropods from the Western Arabian Sea sediment trap - R. Mohan; K. Verma; L. P. Mergulhao; D. K. Sinha; S. Shanvas; M. V. S. Guptha (Geo-Marine Letters, 2006)

Coccolithophores from the central Arabian Sea: Sediment trap results - Lina P. Mergulhao; Rahul Mohan; V. S. N. Murty; M. V. S. Guptha; D. K. Sinha (Journal of Earth System Science, 2006)

Impact of Fertility Variation on Gene Diversity and Drift in two Clonal Seed Orchards of Teak (Tectona grandis Linn. f.) - Mohan Varghese; A. Nicodemus; B. Nagarajan; D. Lindgren (New Forests, 2006)

Changes in the source and transport mechanism of terrigenous input to the Indian sector of Southern Ocean during the late Quaternary and its palaeoceanographic implications - M. Thamban; S. S. Naik; R. Mohan; A. Rajakumar; N. Basavaiah; Witty D’Souza; Sarita Kerkar; M. M. Subramaniam; M. Sudhakar; P. C. Pandey (Journal of Earth System Science, 2005)

Distribution of Persistent Organochlorine Pesticide Residues in Gomti River, India - K. P. Singh; A. Malik; D. Mohan; R. Takroo (Bulletin of Environmental Contamination and Toxicology, 2005)

Persistent Organochlorine Pesticide Residues in Alluvial Groundwater Aquifers of Gangetic Plains, India - K. P. Singh; A. Malik; D. Mohan; S. Sinha (Bulletin of Environmental Contamination and Toxicology, 2005)

Distribution of Polycyclic Aromatic Hydrocarbons in Gomti River System, India - A. Malik; K. P. Singh; D. Mohan; D. K. Patel (Bulletin of Environmental Contamination and Toxicology, 2004)

Rubella virus P90 associates with the cytokinesis regulatory protein Citron-K kinase and the viral infection and constitutive expression of P90 protein both induce cell cycle arrest following S phase in cell culture - C. D. Atreya; S. Kulkarni; K.V. K. Mohan (Archives of Virology, 2004)

Biosorption of inorganic and methyl mercury by a biosorbent from Aspergillus niger - D. Karunasagar; J. Arunachalam; K. Rashmi; J. Naveena Lavanya Latha; P. Maruthi Mohan (World Journal of Microbiology and Biotechnology, 2003)

Purification and characterization of a Ca2+-dependent/calmodulin-stimulated protein kinase from moss chloronema cells - Jacinta S D’Souza; Man Mohan Johri (Journal of Biosciences, 2003)

A Human Vaccine Strain of Lamb Rotavirus (Chinese) NSP4 Gene: Complete Nucleotide Sequence and Phylogenetic Analyses - Ketha V. Krishna Mohan; Sandhya Kulkarni; Roger I. Glass; Bai ZhiSheng; Chintamani D. Atreya (Virus Genes, 2003)

Spectrum of monoclonal gammapathies in Andhra Pradesh - T. Malati; B. Yadagiri; D. Murali Mohan Krishna; V. Shantaram; D. Raghunadharao; K. Subbarao (Indian Journal of Clinical Biochemistry, 2001)

Comparative sequence analysis identified mutations outside the NSP4 cytotoxic domain of tissue culture-adapted ATCC-Wa strain of human rotavirus and a novel inter-species variable domain in its C-terminus - K. V. Krishna Mohan; C. D. Atreya (Archives of Virology, 2000)

The complete primary structure of mouse 20S proteasomes - Laura A. Elenich; D. Nandi; A. Elizabeth Kent; T. Scott McCluskey; M. Cruz; Mohan N. Iyer; Elaine C. Woodward; Christopher W. Conn; Amber L. Ochoa; David B. Ginsburg; J. J. Monaco (Immunogenetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Empirical functions for dependent furrow irrigation variables. - D. Zerihun; Z. Wang; Jan Feyen; J. Mohan Reddy (Irrigation Science, 1997)

Empirical functions for dependent furrow irrigation variables. - D. Zerihun; Jan Feyen; J. Mohan Reddy (Irrigation Science, 1997)